Homogeneous selection and immigration limitation jointly shape brewing- suitable microbiomes in distillery workshops across Maotai town - Shuang Han; Qing He; Youcui Yang; Juan Shen; Chunyan Long; Xiaofei Zou; Haoting Yan; Guang Feng; Gangxiang Fei; Lu Qiao; Kai Feng; Mingqian Liu; et al. (Food Research International, 2026)

Corrigendum to “Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy” [Chem. Eng. J. 495 (2024) 153371] - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2026)

Dual effects of tidal stress on carbon turnover by biochar incorporation in estuarine wetlands: Obscuring the promotion of plant CO2 fixation while magnifying carbon stabilization of sediments - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Lin Liu; Wei Wu; Xiaohua Fu; Lei Wang (Water Research, 2026)

Deriving health-based soil cadmium thresholds in mining-impacted agricultural regions: An integrated deterministic and probabilistic risk assessment - Haoting Tian; Shuangjiao Guo; Zhiming Liu; Xiaohui Yang; Dengfeng Wang; Aijing Yin; Pengbao Wu; Huan Zhang (Journal of Hazardous Materials, 2026)

Characterizing biases in accuracy comparison of multiple snow products by error decomposition over the Tibetan Plateau - Zhanliang Zhu; Xiongpeng Tang; Jianyun Zhang; Chao Gao; Silong Zhang; Lei Liu; Haoting Xu; Yehai Tang; Yanli Liu; Bikui Zhao (Journal of Hydrology, 2025)

Supramolecular self-assembly for probiotic delivery in food system: responsive strategies, multifunctional carriers, future perspectives - Li Song; Haoting Xu; Chaofan Chen; Yubin Zhang; Zihao Zhang; Xiangfeng Chen; Shunxun Liu; Hang Xiao; Qing Gu; Ping Li (Trends in Food Science & Technology, 2025)

Enhanced performance of algal-bacterial granular sludge in treating wastewater under PFOA stress: Synergistic effects and mechanisms - Fahui Ji; Xiaojing Yang; Haoting Quan; Jinxia Liu; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Cyclic organic matter accumulation in a plateau salinized lacustrine basin: Major controls and hydrocarbon significance - Peng Pang; Di Xiao; Kunyu Wu; Songtao Wu; Haoting Xing; Ying Xiong; Rui Liu; Xiucheng Tan (Marine and Petroleum Geology, 2025)

Live-cell imaging of β-galactosidase based on a quinoline-malononitrile-derived AIE probe - Shadi Ali Hassen Ahmed; Xue Gao; Yi Zheng; Haoting Wang; Su Zeng; Hui Liu; Linghui Qian (Analytica Chimica Acta, 2025)

The combined effects of soil moisture and salinity on the spatial differences of soil humification intensity in the Yangtze River estuarine wetlands - Haoyu Dong; Wenxuan Mei; Liwei Qian; Xiaoyu Gao; Haoting Liu; Xiaohua Fu; Lei Wang (Journal of Soils and Sediments, 2025)

Response of key nitrogen removal processes in estuarine salt marshes to different plant harvesting patterns varies significantly across different time scales - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Liwei Qian; Xiaohua Fu; Lei Wang (Journal of Environmental Management, 2025)

Particle size is an important factor influencing the effects of biochar return to woodland soils: An evaluation from the perspective of sapling growth and soil microbial carbon processes - Xiaoyu Gao; Haoting Liu; Wenxuan Mei; Wenwen Zhang; Haoyu Dong; Xiaohua Fu; Mengdi Xie; Yujie Han; Lei Wang (Journal of Environmental Management, 2024)

Enhanced runoff simulation by precise capture of snowmelt variation signals with satellite-based snow products in a high-elevation basin - Zhanliang Zhu; Xiongpeng Tang; Jianyun Zhang; Lei Liu; Chao Gao; Silong Zhang; Guoqing Wang; Junliang Jin; Cuishan Liu; Haoting Xu; Yehai Tang (Journal of Hydrology, 2024)

Cortical microstructural alterations in different stages of Parkinson’s disease - Xueqin Bai; Tao Guo; Xiaojun Guan; Cheng Zhou; Jingjing Wu; Haoting Wu; Xiaocao Liu; Chengqing Wu; Jingwen Chen; Jiaqi Wen; Jianmei Qin; Sijia Tan; et al. (Brain Imaging and Behavior, 2024)

Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2024)

Determinations of methylmercury and mercury methylation/demethylation rate constants in environmental samples using isotope dilution/tracing methods by automatic ethylation-purge and trap-GC-ICP-MS - Yandong Liu; Xueyu Guo; Jinqian Ju; Haoting Gong; Huijing Wang; Lufeng Chen; Yanqun Liu; Pu Wang; Yong Liang (Analytica Chimica Acta, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Exogenous Spermidine Modulates Osmoregulatory Substances and Leaf Stomata to Alleviate the Damage to Lettuce Seedlings Caused by High Temperature Stress - Haoting Huang; Yingyan Han; Jinghong Hao; Xiaoxiao Qin; Chaojie Liu; Shuangxi Fan (Journal of Plant Growth Regulation, 2023)

Cholinergic relevant functional reactivity is associated with dopamine responsiveness of tremor in Parkinson’s disease - Jingjing Wu; Cheng Zhou; Tao Guo; Xiaojun Guan; Ting Gao; Xueqin Bai; Haoting Wu; Jingwen Chen; Jiaqi Wen; Xiaocao Liu; Luyan Gu; Zhe Song; et al. (Brain Imaging and Behavior, 2022)
Tremor in Parkinson’s disease (PD) has distinct responsiveness to dopamine, which is supposed not be exclusively related to dopamine deficiency but has a close relationship with cholinergic system. This phenomenon indicates that cholinergic system may be an important regulatory for distinct dopamine responsiveness of parkinsonian tremor. Through investigating the alterations of cholinergic and dopaminergic network during levodopa administration, we aimed at exploring the mechanisms of differed dopamine responsiveness of parkinsonian tremor. Fifty-two PD patients with tremor were enrolled. MRI scanning, UPDRS III and its sub-symptom scores were collected in OFF and ON status (dopaminergic challenge test). Then, patients were divided into two groups (dopamine-resistant tremor and dopamine-responsive tremor) according to the tremor change rate median score. Dopaminergic and cholinergic network were obtained. LASSO regression was conducted to identify functional connectivity with distinct reactivity during levodopa administration between groups. Afterwards, detailed group comparisons, interaction and correlation analyses were performed. The reactivity of cholinergic connectivity showed the highest possibility to distinguish two groups, especially connectivity of right basal forebrain 123 to right parietal operculum cortex (R.BF123-R.PO). After levodopa administration, connectivity of R.BF123-R.PO was decreased for dopamine-responsive tremor while which remained unchanged for dopamine-resistant tremor. The reactivity of R.BF123-R.PO was negatively correlated with tremor change rate. Reduced cholinergic connectivity to parietal operculum may be an underlying mechanism for the responsive tremor in PD and the distinct cholinergic reactivity of parietal operculum to levodopa may be a core pathophysiology for the differed DA responsiveness of tremor in PD.

An iterative damped least-squares algorithm for simultaneously monitoring the development of hemorrhagic and secondary ischemic lesions in brain injuries - Xuechao Liu; Haoting Li; Hang Ma; Canhua Xu; Bin Yang; Meng Dai; Xiuzhen Dong; Feng Fu (Medical & Biological Engineering & Computing, 2019)